2005
DOI: 10.1089/gte.2005.9.138
|View full text |Cite
|
Sign up to set email alerts
|

Deletions Account for 17% of Pathogenic Germline Alterations in MLH1 and MSH2 in Hereditary Nonpolyposis Colorectal Cancer (HNPCC) Families

Abstract: Hereditary nonpolyposis colorectal cancer (HNPCC) is due to defects in DNA mismatch repair (MMR) genes MSH2, MLH1, MSH6, and to a lesser extent PMS2. Of 466 suspected HNPCC families, we defined 54 index patients with either tumors of high microsatellite instability (MSI-H) and/or loss of expression for either MLH1, MSH2, and/or MSH6, but without a detectable pathogenic point mutation in these genes. This study cohort was augmented to 64 patients by 10 mutation-negative index patients from Amsterdam families wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 35 publications
2
25
0
2
Order By: Relevance
“…Grabowski et al [20] reported that large fragment deletion in hMLH1 and hMSH2 accounts for 17% of all pathogenic mutations, which is almost consistent with the results of our study. The three types of large fragment deletion are in line with the findings reported by Nakagawa et al [21] .…”
Section: Discussionsupporting
confidence: 93%
“…Grabowski et al [20] reported that large fragment deletion in hMLH1 and hMSH2 accounts for 17% of all pathogenic mutations, which is almost consistent with the results of our study. The three types of large fragment deletion are in line with the findings reported by Nakagawa et al [21] .…”
Section: Discussionsupporting
confidence: 93%
“…The present frequency of large genomic deletions, 27%, which is already in the upper range of deletion rates reported for comparable series in the literature 14,[32][33][34] does not include a prevalent founder mutation (Mutation 1 21 ) that had been excluded at the outset. Among the original 81 families from which the present research cohort of 11 families originated, 29 are known to harbor Mutation 1; additionally, 1 family has a genomic deletion of MLH1 Exons 3-5 19 that was independently diagnosed in another member of the same family as part of the present clinic-based cohort.…”
Section: Discussionmentioning
confidence: 48%
“…Deletion or duplication analysis of the MLH1 and MSH2 gene with an MLPA assay was published previously. 32 The MLH1 core promoter is located between c.1-300 and c.1-140 bp. 15,16,33 For amplification and sequencing of the region including c.1 -667 to c.1 -26 bp (Figure 1a and Supplementary Table 1), a standard touchdown PCR protocol 34 was performed.…”
Section: Patients and Materialsmentioning
confidence: 99%